2014
DOI: 10.1542/hpeds.2013-0052
|View full text |Cite
|
Sign up to set email alerts
|

Stevens-Johnson Syndrome, Mucositis, or Something Else?

Abstract: ILLUSTRATIVE CASE EIA is a recurring section of Hospital Pediatrics where expert pediatric hospitalists give their interpretation of the recent evidence in reference to common clinical questions encountered in their daily practice.Stevens-Johnson Syndrome, Mucositis, or Something Else?Stevens-Johnson syndrome (SJS) has been described in the literature as a combination of erythematous blistering skin lesions covering <10% of body surface area and ≥1 mucous membrane erosion.1 SJS is usually triggered by a medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…There is no clear evidence to establish the best therapeutic approach to these cases; most affected individuals received antibiotics or immunosuppressive agents . Based on other reports and our experience, we propose that systemic steroids might help control the hypersensitivity reaction and thereby accelerate healing of mucocutaneous involvement . In our opinion, antibiotic therapy should be reserved for microbiologically confirmed cases and for individuals with signs of pneumonia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There is no clear evidence to establish the best therapeutic approach to these cases; most affected individuals received antibiotics or immunosuppressive agents . Based on other reports and our experience, we propose that systemic steroids might help control the hypersensitivity reaction and thereby accelerate healing of mucocutaneous involvement . In our opinion, antibiotic therapy should be reserved for microbiologically confirmed cases and for individuals with signs of pneumonia.…”
Section: Discussionmentioning
confidence: 92%
“…A search in the PubMed and MEDLINE databases for an association between mucositis, EM, or SJS and C. pneumoniae produced 20 reported cases, which are summarized in Table . Drawing on similarities with MIRM, we have included a chlamydia ‐induced rash and mucositis (CIRM) column, where we classify these cases in terms of extensive spread (severe) or cases in which no skin lesions were present (without rash).…”
Section: Discussionmentioning
confidence: 99%
“…Steroids have been demonstrated to be beneficial in some patients in reducing the severity of mucositis. 3 The role of intravenous immunoglobulin (IVIG) is still under debate, and it carries the risk of transfusion reactions and anaphylaxis. In a review by Meyer et al, 4 among 32 confirmed cases of MPAM, 31% showed improvement with corticosteroids and IVIG was used in 9% of cases.…”
Section: To the Editormentioning
confidence: 99%
“…Sometimes, the mucous membrane erosions are the only manifestation of a drug reaction, without significant skin involvement. This has been classified as “atypical SJS” or mucositis . In these clinical entities, the duration from the drug intake to the first onset of a symptom may range between few hours and 45 days, and the recovery time may be very long because re‐epithelization of the skin or mucosa could be achieved within several weeks .…”
Section: What Is New and Conclusionmentioning
confidence: 99%
“…This has been classified as "atypical SJS" or mucositis. 23 In these clinical entities, the duration from the drug intake to the first onset of a symptom may range between few hours and 45 days, and the recovery time may be very long because re-epithelization of the skin or mucosa could be achieved within several weeks. 22,24 This can happen even after a single dose of drug, as reported, for example, for ibuprofen 25 and etoricoxib 19 and as in our case.…”
Section: Case Descriptionmentioning
confidence: 99%